New Opportunities Offered by Cubesats for Space Research in Latin America: The Suchai Project Case - Stepanova, M; Romanova, N (Elsevier Ltd, 2016)
During the last decade, a very small-standardized satellite, the Cubesat, emerged as a low-cost fast-development tool for space and technology research. Although its genesis is related to education, the change in paradigm presented by this satellite platform has motivated several countries, institutions, and companies to invest in a variety of technologies, aimed at improving Cubesat capabilities, while lowering costs of space missions. Following that trend, Latin American institutions, mostly universities, has started to develop Cubesat missions. This article describes some of the Latin American projects in this area. In particular, we discuss the achievements and scientific grounds upon which the first Cubesat projects in Chile were based and the implications that those projects have had on pursuing satellite-based research in the country and in collaboration with other countries of the region. © 2016 COSPAR